Skinfold thicknesses method to analyse body fat in hemodialysis patients: comparison with dual energy x-ray absorptiometry - Viviane O Leal; Cristiane Moraes; Milena B Stockler-Pinto; Amanda Barros; Najla E Farage; Denise Mafra (The Korean Society of Nephrology, 2012)
Nutritional status is a major determinant of the outcome of hemodialysis (HD) patients. While protein wasting is associated with morbidity and mortality, high fat mass and central adiposity is also observed in HD population and, related to metabolic disorders. Therefore, body composition assessment is a key point to provide adequate nutritional care to these patients. In this way, practical and reliable indicators of body composition are needed for clinical purposes. Thus, the objective of this study was to evaluate the use of anthropometry as an alternative to dual energy X-ray absorptiometry (DXA), considered the reference method to evaluate body fat in HD patients. Thirty-nine HD patients (52.7±11.3 years, 24 men, BMI, 23.7±4.0 kg/m2, urea clearance (Kt/Vsp) of 1.47±0.22 and 64.1±46.1 months on HD) were studied. Percentage of body fat (%BF) was performed by DXA scans (Prodigy Advanc Plus, Lunar Corp, Madison, WI, USA) and anthropometry (biceps, triceps, subscapular and suprailiac skinfold thicknesses) after a HD session. Body density was calculated using the formula of Durnin and Womersley (1974) and the %BF was calculated by Siri´s equation (Siri, 1961). The reference values for %BF were considered (Lohman et al., 1991). The mean of %BF assessed by anthopometry and DXA was 25.2±6.9% and 26.8±8.3% for men and 32.8±6.3% and 31.5±8.7% for women, respectively. The most of HD patients presented high %BF (≥25% for men and ≥32% for women): 59.0% by anthropometry and 56.4% by DXA. The paired analysis showed that the %BF assessment was not different when evaluated by anthropometry or DXA methods (p=0.6). The kappa coefficient between DXA and anthropometry was 0.42 (p<0.0001), which is considered as good correlation between two methods. In conclusion, the simple method of skinfold thicknesses is reliable to assess body fat in HD patients when compared to DXA.